Improvement to East African style experimental huts allows for more effective evaluation of vector control products for protection against vector-borne diseases - Portwood, Natalie; Sumari, Godwin; Matowo, Johnson; Azizi, Salum; Manunda, Baltazari; Ezekia, Kisengwa; Mosha, Franklin W.; Messenger, Louisa A.; Rowland, Mark W.; Mbewe, Njelembo J. (Parasites & vectors, 2025)
Background: East African style experimental huts have been used in Tanzania since 1963 to evaluate vector control interventions such as insecticide-treated nets and indoor residual spraying. Over time, these huts have been modified to include eave baffles to minimise mosquito escape. In this study, we evaluated the impact of increasing baffle size and using netting to funnel mosquito entry into the room and prevent escape. We also explored mosquito entry behaviour using a sticky trap positioned on the hut exterior to determine if this behaviour could be leveraged for vector control. Methods: This study was conducted in Moshi, Tanzania and included two trials. In trial one, we compared the original huts with baffles with small exit holes (4 × 110 cm at the wide end nearest the eave gap and 2 × 2 cm at the narrow funnel end) to those with a larger size of baffle exit hole (20 × 120 cm at the wide end and 4 × 10 cm at the narrow end). In trial two, we compared huts with a sticky trap on the exterior wall to those without. Data analyses used logistic regression models to compare mosquito entry, blood-feeding rates and exophily, adjusting for variation between huts, cows (for blood-feeding) and days of the trial. Results: Larger eave baffles significantly increased entry of Anopheles gambiae Kisumu mosquitoes into huts [p = 0.01, adjusted odds ratio (AOR) 2.1, 95% confidence interval (CI) 1.2–3.8]. Blood-feeding rates were also significantly higher in huts with the larger baffle size compared to those with the original baffle size [p = 0.001, AOR 16.9 95% CI 4.9–59.0]. In trial two, 16% (95 CI 13.3–19.6) of An. gambiae Kisumu and 8% (95 CI: 6.3–10.5) of Anopheles arabiensis populations were collected on the sticky traps, significantly reducing mosquito entry into huts. With the presence of sticky traps, blood-feeding was inhibited by 12.7% for An. arabiensis and 32.6% for An. gambiae Kisumu. Conclusions: The results of this study support the use of larger baffle sizes in East African huts to capture larger numbers of mosquitoes and improve the evaluation of vector control tools. Although only a small proportion of mosquitoes were found to have had direct contact with the exterior of the hut before entry, the presence of sticky traps still reduced blood-feeding rates by limiting the entry of host-seeking mosquitoes.